2022
DOI: 10.1016/j.jaip.2021.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns and Treatment Adherence in Patients with Asthma During the COVID-19 Pandemic

Abstract: Background The COVID-19 pandemic has witnessed a reduction in asthma exacerbations across the UK. Several factors may underpin this, including reduced transmission of seasonal viruses and improved adherence to inhaled corticosteroids (ICS). However, little is known about how ICS use has changed during the pandemic. Objective To identify prescribing patterns for asthmatics during the pandemic. Methods Using the OpenPrescribing database, we ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…A recent study from England suggested only a modest increase in adherence to Inhaled Corticosteroids (ICS) medication in the first year of the pandemic primarily driven by increased prescription in March 2020. 31 Another study from England suggests that medication use declined during the first eight months of the pandemic. 32 Studies from the US have also suggested decreased adherence to controller medications amongst patients with asthma for both children 33 and adults 34 during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from England suggested only a modest increase in adherence to Inhaled Corticosteroids (ICS) medication in the first year of the pandemic primarily driven by increased prescription in March 2020. 31 Another study from England suggests that medication use declined during the first eight months of the pandemic. 32 Studies from the US have also suggested decreased adherence to controller medications amongst patients with asthma for both children 33 and adults 34 during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Relatedly, there is some evidence that the reductions in asthma exacerbations observed during the pandemic may also have been partially driven by increased disease awareness and medication adherence. [30][31][32] An analysis of controller inhaler usage among patients with asthma or chronic obstructive pulmonary disease (COPD) found a 14.5% increase in medication adherence from the beginning of January 2020 to the end of March 2020. 31 Patients with asthma may have thought they had a higher risk of contracting severe COVID-19 disease, which could contribute to positive changes in medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors could explain this, including a fall in urban air pollution levels and/or a change in patient behavior leading to an improvement in adherence to ICSs. 99 However, it is possible that the nonpharmacologic interventions of increased hand washing and mask wearing, aimed at reducing transmission of severe acute respiratory syndrome coronavirus 2, will ultimately prove to be the most effective intervention against seasonal virusinduced asthma exacerbations since the introduction of ICSs almost half a century ago. For example, in New Zealand during the first wave of the pandemic, the usual winter influenza surge was essentially eliminated, with a 99.9% reduction in influenza virus detections, and a 74.6% reduction in RV infections as compared with previous years.…”
Section: Lessons Learned From the Covid-19 Pandemicmentioning
confidence: 99%